Too hard to handle - Walker, Julie Ann (Walker, Julie Ann. Black Knights Inc., 2015)
"Dan "The Man" Currington is back in fighting form with a mission that takes him four thousand miles south of BKI headquarters, high in the Andes Mountains of Peru. He's hot on the trail of a rogue CIA agent selling classified government secrets to the highest bidder, when Penni DePaul arrives on the scene. Suddenly the stakes are higher, and keeping Penni safe becomes Dan's number one priority. A lot has changed since former Secret Service Agent Penni DePaul last saw Dan. Now a civilian, she's excited about what the future might hold. But before she can grab onto that future with both hands, she has to tie up some loose ends--namely, Dan Currington, the man she just can't forget. And a secret that's going to change both their lives--if they can stay alive, that is" --